2021
DOI: 10.1371/journal.pone.0253423
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of routine childhood vaccination in low- and middle-income countries, 1978–2021: Protocol for a scoping review to map methodologic gaps and determinants

Abstract: The literature on the timeliness of childhood vaccination (i.e. vaccination at the earliest appropriate age) in low-and middle-income countries has important measurement and methodological issues that may limit their usefulness and cross comparison. We aim to conduct a comprehensive scoping review to map the existing literature with a key focus on how the literature on vaccination timeliness has evolved, how it has been defined or measured, and what determinants have been explored in the period spanning the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Following descriptive qualitative content analysis, summary of the key findings will be presented using tables, charts and geospatial map(s) to aid visualisation. 46 More specifically, geospatial mapping will help highlight gaps in coverage of regulatory standards and guidance for regulating the use of health applications for self-management across countries within the WHO African Region.…”
Section: Methodsmentioning
confidence: 99%
“…Following descriptive qualitative content analysis, summary of the key findings will be presented using tables, charts and geospatial map(s) to aid visualisation. 46 More specifically, geospatial mapping will help highlight gaps in coverage of regulatory standards and guidance for regulating the use of health applications for self-management across countries within the WHO African Region.…”
Section: Methodsmentioning
confidence: 99%
“…The review is reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) (S1 Checklist) [15]. Since registration of scoping reviews are currently not accepted in PROSPERO, we published the review protocol a priori in a peer-review journal [16]. The review process did not deviate from the previously published protocol.…”
Section: Measurement Gapsmentioning
confidence: 99%
“…In children, timely immunization is an important strategy for reducing the global burden of VPDs (7,8). Adherence to timely immunization in children can dramatically reduce the incidence, prevalence, and mortality of various types of VPDs (8).…”
Section: Introductionmentioning
confidence: 99%
“…In children, timely immunization is an important strategy for reducing the global burden of VPDs (7,8). Adherence to timely immunization in children can dramatically reduce the incidence, prevalence, and mortality of various types of VPDs (8). Timely immunization in children refers to immunizing a child within 28 or 30 days of the scheduled immunization date (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation